Silagem de girassol para vacas leiteiras em lactação - Leonardo Andrade Leite (2007)
The objectives of this study were to compare intake and aparent digestibility of dry matter, organic matter, neutral detergent fiber, acid detergent fiber and intake of crude protein of Holstein cows fed sunflower silage (SS) in replacement of corn silage (CS) in the diets. Five ruminal cannulated cows, 60 to 82 days in milk, were arranged in a 5X5 Latin Square design. The treatments were either 100% corn silage (100CS) or 34% sunflower silage plus 66% corn silage (34SS) or 66% sunflower silage plus 34% corn silage (66SS) or 100% sunflower silage (100SS) or 100% corn silage plus whole cotton seed (CS-WCS). The diets were formulated according NRC 2001, to be isoproteic. Dry matter intake, intake of organic matter, intake and aparent digestibility of neutral detergent fiber and acid detergent fiber were lower for 100SS compared to 100CS (P<.05). For the values of aparent digestibility of organic matter, only treatment 100SS was diferent of others. However, increasing levels of corn silage in the diets increased the dry matter intake and organic matter intake. Parcial replacement of the corn silage with sunflower silage could be viable option for lactation cows diets.